Suppressed Vascular Leakage and Myocardial Edema Improve Outcome From Myocardial Infarction - Li, Xiujuan (Front Physiol, 2020)
AIM: The acute phase of myocardial infarction (MI) is accompanied by edema contributing to tissue damage and disease outcome. Here, we aimed to identify the mechanism whereby vascular endothelial growth factor (VEGF)-A induces myocardial edema in the acute phase of MI to eventually promote development of therapeutics to specifically suppress VEGFA-regulated vascular permeability while preserving collateral vessel formation. METHODS AND RESULTS: VEGFA regulates vascular permeability and edema by activation of VEGF receptor-2 (VEGFR2), leading to induction of several signaling pathways including the cytoplasmic tyrosine kinase c-Src. The activated c-Src in turn phosphorylates vascular endothelial (VE)-cadherin, leading to dissociation of endothelial adherens junctions. A particular tyrosine at position 949 in mouse VEGFR2 has been shown to be required for activation of c-Src. Wild-type mice and mice with phenylalanine replacing tyrosine (Y) 949 in VEGFR2 (Vegfr2(Y949F/Y949F)) were challenged with MI through permanent ligation of the left anterior descending coronary artery. The infarct size was similar in wild-type and mutant mice, but left ventricular wall edema and fibrinogen deposition, indicative of vascular leakage, were reduced in the Vegfr2(Y949F/Y949F) strain. When challenged with large infarcts, the Vegfr2(Y949F/Y949F) mice survived significantly better than the wild-type strain. Moreover, neutrophil infiltration and levels of myeloperoxidase were low in the infarcted Vegfr2(Y949F/Y949F) hearts, correlating with improved survival. In vivo tyrosine phosphorylation of VE-cadherin at Y685, implicated in regulation of vascular permeability, was induced by circulating VEGFA in the wild-type but remained at baseline levels in the Vegfr2(Y949F/Y949F) hearts. CONCLUSION: Suppression of VEGFA/VEGFR2-regulated vascular permeability leads to diminished edema without affecting vascular density correlating with improved myocardial parameters and survival after MI.